Sistem Monitoring Kanopi Pintar Secara Real-time Berbasis IOT - Abdul Refli Gunawan; Aris Gunaryati; Ucuk Darusalam (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Daily drying of clothes sometimes has problems when it rains. This makes the clothes wet again. A smart canopy system that can detect rain is needed to maximize daily work. In this study, a real-time smart canopy monitoring system was designed based on the Internet of Things and the ThingSpeak cloud platform that can monitor the status of the canopy and rainfall. This system uses a water sensor to detect rainwater. The maximum value of the sensor is 1024. Data processing uses NodeMCU which functions as a medium for processing and sending data. From the research conducted, the average time received by ThingSpeak is 1 second. The system is web-based, so monitoring is easy. Determination of the smart canopy action is determined using the fuzzy logic method with accuracy in determining the action of 100%.